2019
DOI: 10.1038/s41598-019-47804-2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impacts of climate change on riverine thermal regimes in western Canada’s largest Pacific watershed

Abstract: Quantification of climate change impacts on the thermal regimes of rivers in British Columbia (BC) is crucial given their importance to aquatic ecosystems. Using the Air2Stream model, we investigate the impact of both air temperature and streamflow changes on river water temperatures from 1950 to 2015 across BC’s 234,000 km 2 Fraser River Basin (FRB). Model results show the FRB’s summer water temperatures rose by nearly 1.0 °C during 1950–2015 with 0.47 °C spread across 17 river sites. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 50 publications
(69 reference statements)
3
33
0
Order By: Relevance
“…Nevertheless, the increases in the surface water temperature and depth average temperature in summer were relatively large (0.29°C/yr and 0.13°C/yr, respectively) with statistical significance (p < 0.05), which is thought to be because, due to the increased air temperature, factors such as solar radiation and tropical nights also affect heat energy transfer and accumulation in water bodies, and these effects are especially strong in lakes and other water bodies with long retention times [14]. Islam et al [51] used the Air2Stream model, which is a state-of-the-art hybrid river water temperature model relying on heat budgets with a similar formulation and approach as a lake surface temperature model, to investigate changes in air and water temperature between 1950 and 2015 at the Fraser River Basin in British Columbia, Canada, and reported that the summer water temperature increased by approximately 1°C in 17 rivers during this time. Kwak et al [52] modeled water temperature in the Fourchue River in Quebec, Canada using the CMIP5 climate model and RCP 2.6, 4.5, and 8.5 climate change scenarios, and predicted that median water temperatures in June would increase by 0.2-0.7°C, resulting in favorable temperatures for trout growth and altering the habitats of coldwater species.…”
Section: Comparison Of Air and Water Temperature Trends At Lakementioning
confidence: 98%
“…Nevertheless, the increases in the surface water temperature and depth average temperature in summer were relatively large (0.29°C/yr and 0.13°C/yr, respectively) with statistical significance (p < 0.05), which is thought to be because, due to the increased air temperature, factors such as solar radiation and tropical nights also affect heat energy transfer and accumulation in water bodies, and these effects are especially strong in lakes and other water bodies with long retention times [14]. Islam et al [51] used the Air2Stream model, which is a state-of-the-art hybrid river water temperature model relying on heat budgets with a similar formulation and approach as a lake surface temperature model, to investigate changes in air and water temperature between 1950 and 2015 at the Fraser River Basin in British Columbia, Canada, and reported that the summer water temperature increased by approximately 1°C in 17 rivers during this time. Kwak et al [52] modeled water temperature in the Fourchue River in Quebec, Canada using the CMIP5 climate model and RCP 2.6, 4.5, and 8.5 climate change scenarios, and predicted that median water temperatures in June would increase by 0.2-0.7°C, resulting in favorable temperatures for trout growth and altering the habitats of coldwater species.…”
Section: Comparison Of Air and Water Temperature Trends At Lakementioning
confidence: 98%
“…Water temperature (WT) is a good indicator of both changes in air temperature (AT) and ways of river supply (Bates et al, 2008;Ficklin et al, 2013;Goulden et al, 2009;Isaak et al, 2012;Koutsoyiannis and Montanari, 2007;Ul Islam et al, 2019;Zhu et al, 2018). Hydrological regime (river regime) is a characteristic, rhythmic course of hydrological phenomena in the river in the yearly cycle, established on the basis of many years of observation.…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, water temperature studies are of great practical importance, as optimization and appropriate management of fisheries requires determining both spatial and temporal water temperature dynamics, particularly in streams inhabited by ecologically valuable fish species (Malcolm et al 2008;Broadmeadow et al 2011). Apart from issues associated with fisheries and aquatic ecology water temperature was commonly used in recent years as a climate change indicator (Isaak et al 2012;Ficklin et al 2013;Ul Islam et al 2019), as well as a tracer of groundwater flow patterns (Anderson 2015). Finally, temperature monitoring seems to be highly valuable in the case of rivers and streams flowing in the proximity of sprawling urbanized areas, where changes in thermal characteristics can be used in the evaluation of future anthropopressure.…”
Section: Introductionmentioning
confidence: 99%